Taxonomic notes about the genus Nephelotus Pascoe, 1866 (Coleoptera, Cerambycidae, Lamiinae) - Vitali, Francesco; Chemin, Gerard (Zootaxa, 2022)
Paranhammus Breuning, 1944 and Mimonephelotes Breuning, 1970 (both monotypic genera) are considered junior synonyms of Nephelotus Pascoe, 1866. Mimanhammus Breuning, 1971 is considered an unnecessary replacement name for Mimonephelotes, despite the similarity to Mimonephelotus Breuning, 1940. Resultant combinations are Nephelotus enganensis (Breuning, 1970) and Nephelotus marcipor (Newman, 1842). Anhammus luzonicus Breuning, 1982 is considered a junior synonym of N. enganensis.